Intraoperative floppy iris syndrome – epidemiology and clinical assessment - Wierzchowski, Tomasz; Wilczynski, Michał; Palenga-Pydyn, Dorota; Synder, Aleksandra; Omulecki, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Purpose : To assess the incidence, and to identify medications and clinical features associated with intraoperative floppy iris syndrome in patients undergoing cataract surgery. Material and methods : The non-randomized, observational, prospective study was performed in 616 eyes (610 patients) after cataract surgery to determine the incidence of intraoperative floppy iris syndrome and the medications associated with its higher prevalence. We used a slit lamp adapted optical coherence tomography to evaluate anterior segment of 155 eyes (154 patients), measuring pupil diameter before and after the use of mydriatics and assessing the pre-dilated iris thickness at the dilator and sphincter muscle region. Results : The overall incidence of intraoperative floppy iris syndrome was 4% (25/616 eyes). The highest prevalence of intraoperative floppy iris syndrome was shown in patients exposed to tamsulosin (39%). Pupil diameter in mm before and after mydriasis was significantly smaller in patients with intraoperative floppy iris syndrome as compared to the syndrome-free ones (pre-dilated – 1.85 ± 0.43 vs. 2.16 ± 0.37; p < 0.01; dilated – 5.04 ± 1.01 vs. 5.70 ± 0.87; p 0.05). Significantly thinner iris in dilator muscle region was found in patients with intraoperative floppy iris syndrome as compared to the syndrome-free ones (409.9 ± 55.7 vs. 448.6 ± 55.8; p < 0.05). The presence of intraoperative floppy iris syndrome was correlated with a higher risk of intraoperative complications. Conclusions : Patients with intraoperative floppy iris syndrome have decreased pupil diameter and a thinner iris in dilator muscle region. Slit lamp optical coherence tomography is a useful device to preoperatively detect clinical features associated with intraoperative floppy iris syndrome. These findings may warn the surgeon of potential intra-operative difficulties.